2015
DOI: 10.1111/nep.12414
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of clinical presentation of congenital anomalies of the kidney and urinary tract among infants and children

Abstract: CAKUT is a clinically heterogeneous group of diseases with diverse clinical phenotypes. More efforts should be aimed at improving antenatal detection as well as classification with comprehensive reference to the clinical, genetic and molecular features of the diseases. The high frequency of familial and syndromic CAKUT among studied patients is seemingly a convincing reason to pursue the underlying genetic defect in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 22 publications
3
39
1
2
Order By: Relevance
“…Bondagji [10] found associated nonrenal anomalies in 26.2% of cases and Soliman et al [8] in 31.8% of cases. The incidence of the different types of CAKUT in the current study and other studies is shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bondagji [10] found associated nonrenal anomalies in 26.2% of cases and Soliman et al [8] in 31.8% of cases. The incidence of the different types of CAKUT in the current study and other studies is shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…CAKUT also accounts for 7% of adult ESRD worldwide [8]. CAKUT is seen in 1 in 500 newborns [2] and in 0.3–1.6 per 1,000 live born and stillborn neonates [9].…”
Section: Discussionmentioning
confidence: 99%
“…Many of them like hypoplasia, ectopic kidneys, and anomalies in shape can be asymptomatic and detected incidentally in adults. Others like renal agenesis, MCDK, bilateral PUJO and cystic renal diseases can present early either antenatally with oligohydramnios or later with urinary tract infection, hypertension, proteinuria, renal impairment, abdominal mass, hematuria or stones [6] . Antenatal screening ultrasonography (US) allows demonstration of fetal kidneys and urinary bladder from early second trimester and enables to detect a number of major congenital anomalies of the urinary system.…”
Section: Approachmentioning
confidence: 99%
“…Among anomalies found at prenatal screening, CAKUT is present in 20%-30% of the cases. 13,14 Renal function ranges from normal to ESRD, but most patients have some degree of impaired kidney function. Urine analysis in general shows no cells and a proteinuria of ,1 g/24 h. Occasionally, renal biopsies are performed in patients that do not present with CAKUT, with the histologic diagnosis often being variable and nonspecific.…”
Section: Hnf1b-associated Kidney Diseasementioning
confidence: 99%